Optical genome mapping with whole genome sequencing identifies complex chromosomal structural variations in acute leukemia - Tsai, Meng-Ju Melody; Kao, Hsiao-Jung; Chen, Hsiao-Huei; Yu, Chih-Hsiang; Chien, Yin-Hsiu; Hwu, Wuh-Liang; Kwok, Pui-Yan; Lee, Ni-Chung; Yang, Yung-Li (Frontiers in Genetics, 2025)
IntroductionChromosomal structural variations (SVs) play an important role in the formation of human cancers, including leukemias. However, many complex SVs cannot be identified by conventional tools, including karyotyping, fluorescence in situ hybridization, microarrays, and multiplex ligation-dependent probe amplification (MLPA).MethodsOptical genome mapping (OGM) and whole genome sequencing (WGS) were employed to analyze five leukemia samples with SVs detected by karyotyping, MLPA, and RNA sequencing (RNA-seq). OGM was performed using the Saphyr chip on a Bionano Saphyr system. Copy number variation and rare variant assembly analyses were performed with Bionano software v3.7. WGS was analyzed by the Manta program for SVs.ResultsThe leukemia samples had an average of 477 insertions, 457 deletions, and 32 inversions, which were significantly greater than those of the normal blood samples (p = 0.016, 0.028, and 0.028, respectively). In Case 1, OGM detected a sequential translocation between chromosomes 5, 8, 12, and 21 and ETV6::RUNX1 and BCAT1::BAALC gene fusions. Case 2 had two pathogenic SVs and a BCR::ABL1 fusion. Case 3 had one pathogenic SV and an IGH::DUSP22 fusion. Case 4 had two pathogenic SVs and a CBFB::MYH11 fusion. Case 5 had an STIL::TAL1 fusion. All breakpoint sequences were defined by WGS. An IGH::DUX4 fusion previously found by RNA-seq in Case 3 was not confirmed because DUX4, which has multiple pseudogenes, was refractory to OGM and WGS analyses.ConclusionOGM is a fundamental tool that complements G-banding analysis in identifying complex SVs in leukemia samples, and WGS effectively closes the gaps in OGM mapping.